U.S. Navy codebreakers, linguists, and intelligence officers against Japan, 1910-1941 : a biographical dictionary - Maffeo, Steven E. (Rowman and Littlefield, 2016)
This unique reference presents 59 biographies of people who were key to the sea services being reasonably prepared to fight the Japanese Empire when the Second World War broke out, and whose advanced work proved crucial. These intelligence pioneers invented techniques, procedures, and equipment from scratch, not only allowing the United States to hold its own in the Pacific despite the loss of most of its Fleet at Pearl Harbor, but also laying the foundation of today's intelligence methods and agencies.